Peran Generasi Muda dalam Pemulihan Gejolak Masa Depan Pertanian Indonesia: The Role of Young Generation in Recovery From the Future Turmoil of Indonesian Agriculture - Rusfa, Fama Manawa Salwa; Rozaki , Zuhud; Wulandari, Retno; Azzahra, Isni (Universitas Muhammadiyah Yogyakarta, 2024)
Indonesian agriculture faces complex future challenges and turmoil. In this context, the role of the younger generation is crucial to the recovery of the agricultural sector. This article examines the active contribution of the younger generation in shaping the future of Indonesian agriculture through innovation, technology and sustainability. The younger generation is recognized as an agent of change and brings a new spirit in the implementation of modern agricultural practices. You are active in applying information technology, developing sustainable business models, and capitalizing on new economic opportunities. In addition, the role of education and training of the younger generation in providing knowledge to traditional farmers is the focus of this article. Therefore, this research highlights the importance of collaboration between the younger generation, the government, and the private sector to create an enabling environment for innovation and sustainable growth in Indonesia's agricultural sector. Through the active role of the younger generation, Indonesian agriculture is expected to overcome future disruptions and develop economic and environmental sustainability. The role of the younger generation is crucial in the future recovery and transformation of Indonesia's agriculture sector, which is currently in a turbulent state. This article discusses the important contribution of the younger generation in addressing agricultural challenges, with a focus on innovation, technology and sustainability. The younger generation is seen as a driving force for change, introducing advanced technologies to improve efficiency and productivity in agriculture. In addition, we actively seek to develop sustainable business models that combine economic, social and ecological aspects. The article also highlights the important role of youth in educating and training traditional farmers by ensuring capacity building and adoption of modern practices. Through cooperation between the younger generation, the government, and the private sector, Indonesian agriculture is expected to achieve positive changes that have a long-term impact to overcome future disruptions and achieve sustainable growth.